KEPASTIAN HUKUM TERHADAP PEMBATALAN PUTUSAN BADAN PENYELESAIAN SENGKETA KONSUMEN YANG TIDAK MEMENUHI SYARAT FORMIL MENURUT PENGADILAN NEGERI KARAWANG - Angeline Monica Natalie Affendi (2023)
The government continues to strive to increase awareness regarding consumer protection in Indonesia by establishing various institutions mandated by Law Number 8 of 1999 concerning Consumer Protection (Law 08/1999). Badan Penyelesaian Sengketa Konsumen (BPSK) is a body established with the authority to handle and resolve consumer disputes through mediation or conciliation or arbitration. In the case of consumer dispute resolution, there are conditions that must be met according to the formal law. In terms of consumer dispute resolution, there are still many law enforcers who do not understand the formal law, resulting in decisions that do not meet formal requirements. One of the cases that occurred was in Decision Number 1/Pdt.Sus-BPSK/2019/PN.Kwg where the BPSK Karawang decision was objected to by the entrepreneur because of an alleged violation of formal requirements. This research is a normative juridical type with statutory and case approaches. Data was collected by means of a literature study and presented qualitatively. The results of the study showed that the judge's consideration to cancel the BPSK Karawang decision was due to not fulfilling two things, namely the absence of the entrepreneur approval to carry out dispute resolution at BPSK and in the BPSK decision there was no description of what dispute resolution mechanism was taken. Then the cancellation of the BPSK decision resulted in legal uncertainty because in Law 08/1999, the BPSK decision characteristics are final and binding. So that in terms of consumer protection, it is necessary to pay attention to the forms of protection provided starting from the legislative process for the formation of regulations that are clearly formulated and from the dispute resolution process, it is necessary to pay attention to the applicable laws and regulations as a form of embodiment of legal certainty. Keywords: Legal Certainty, Cancellation of BPSK Decision, Formal Requirements, Consumer Protection